If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(x + -7)(2x + -5) = 0 Reorder the terms: 2x(-7 + x)(2x + -5) = 0 Reorder the terms: 2x(-7 + x)(-5 + 2x) = 0 Multiply (-7 + x) * (-5 + 2x) 2x(-7(-5 + 2x) + x(-5 + 2x)) = 0 2x((-5 * -7 + 2x * -7) + x(-5 + 2x)) = 0 2x((35 + -14x) + x(-5 + 2x)) = 0 2x(35 + -14x + (-5 * x + 2x * x)) = 0 2x(35 + -14x + (-5x + 2x2)) = 0 Combine like terms: -14x + -5x = -19x 2x(35 + -19x + 2x2) = 0 (35 * 2x + -19x * 2x + 2x2 * 2x) = 0 (70x + -38x2 + 4x3) = 0 Solving 70x + -38x2 + 4x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2x'. 2x(35 + -19x + 2x2) = 0 Factor a trinomial. 2x((5 + -2x)(7 + -1x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(5 + -2x)' equal to zero and attempt to solve: Simplifying 5 + -2x = 0 Solving 5 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 0 + -5 -2x = 0 + -5 Combine like terms: 0 + -5 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5Subproblem 3
Set the factor '(7 + -1x)' equal to zero and attempt to solve: Simplifying 7 + -1x = 0 Solving 7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 0 + -7 -1x = 0 + -7 Combine like terms: 0 + -7 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7Solution
x = {0, 2.5, 7}
| 2n^3-14n^2+24n=0 | | 48x-96=x-30-10x*3 | | y-10=5.5(x-2) | | 7x+9=4x+39 | | Log(5)25=3x-5 | | 8a^2+65a+8=0 | | x+24=45 | | 2/x-14=3/4x | | 2-6t+7+3t= | | 4-6y-7+y= | | 5x+6=-7+126 | | -2(10-s+1)=-21 | | 8a-b=2a+6b | | 1350=(x+25+25)*(x+25)-(x+25)*(x) | | 103+2x+3x+10+12=180 | | s^2+6s-9=0 | | 4-3.68=.32 | | -38=-7x+x+10 | | 7(2+p-5)=14 | | 6=-2x+4x+2 | | 8(x-4)=5x-11 | | 2.3x^2-0.1x-1.2= | | 8(x+4)=5x-11 | | 20x-15+38z=0 | | 2a-6b=-34 | | 4/3(12x-24)=x-5(6-2x) | | 1500=25(n+40) | | 4X+10+x=15 | | 3x+32=-11 | | 103+2x+3x+10+12= | | 5x-7y=5 | | y+2*2y-3= |